Interest in patient navigation chatbots: a cross-sectional survey study - A. Luke MacNeill; Alison Luke; Shelley Doucet (Frontiers in Digital Health, 2026)
Introduction Chatbots are accessible and cost-effective tools that may be able to provide navigation support to people who lack access to conventional patient navigation services. To date, little is known about people's interest in using chatbots for patient navigation. It is also unclear what specific types of support people would like to see incorporated into patient navigation chatbots. The purpose of this study was to gain insight into these topics. Methods Participants were recruited through the Prolific research platform. They completed a cross-sectional survey that captured information on respondent characteristics, general interest in using a patient navigation chatbot, and interest in various navigation support functions. Data were analyzed using descriptive statistics and ANOVA and hierarchical regression statistical tests. Results A total of 276 participants (141 women; M age = 38.99 years, SD = 12.90) were included in the analysis. In general, participants were moderately interested in using a patient navigation chatbot. They had greater interest in functions related to care coordination, linkage to services and resources, and general education than functions related to needs assessment and treatment support. Interest varied by certain respondent characteristics, particularly demographic and personality factors. Discussion The findings from this study will help inform the design and marketing of patient navigation chatbots. The effective implementation of this technology may fill some of the accessibility gaps that characterize conventional patient navigation programs.